The relationship between 3S (Seiri, Seiton, and Seiso) behaviors, and psychological distress and work engagement - Sawajima, Tomoko; Nagata, Tomohisa; Odagami, Kiminori; Mori, Takahiro; Adi, Nuri Purwito; Mori, Koji (Frontiers in Public Health, 2025)
ObjectivesThis study aimed to examine the relationship between 3S [Seiri (Sort), Seiton (Set), and Seiso (Shine)] behaviors in the workplace and workers’ psychological distress and work engagement.MethodsA prospective cohort study was conducted using an online survey among workers in Japan (n = 9,451 at baseline; n = 6,156 at follow-up). At baseline, participants were asked whether they routinely practiced 3S behaviors in the workplace every day. Psychological distress was measured using the Japanese version of Kessler 6-Item Psychological Distress Scale (K6), and work engagement was assessed using the Japanese version of the Utrecht Work Engagement Scale (UWES-9) at baseline and follow-up. Covariates included industry type and K6/UWES-9 at baseline. Multiple regression analyses were conducted to evaluate the relationship between 3S behaviors at baseline and K6/UWES-9 at follow-up.ResultsThere were 3,862 (62.7%) workers who practiced 3S behaviors. Workers who did not practice 3S behaviors had significantly higher psychological distress than those who did (standardized coefficient = 0.03, p = 0.006). There was no statistical difference in work engagement between workers who practiced 3S behaviors and those who did not (standardized coefficient = −0.01, p = 0.339).ConclusionDaily practice of 3S behaviors was related to lower psychological distress among workers, suggesting that 3S may serve not only as a tool for quality management but also as a potential strategy for improving mental health in the workplace.